Metal-free synthesis of biarenes via photoextrusion in di(tri)aryl phosphates - Qrareya, Hisham; Meazza, Lorenzo; Protti, Stefano; Fagnoni, Maurizio (Beilstein Journal of Organic Chemistry, 2020)
A metal-free route for the synthesis of biarenes has been developed. The approach is based on the photoextrusion of a phosphate moiety occurring upon irradiation of biaryl- and triaryl phosphates. The reaction involves an exciplex as the intermediate and it is especially suitable for the preparation of electron-rich biarenes.
Keywords: aryl phosphates; biarenes; metal-free synthesis; photochemistry; photoextrusion